(untitled) (World Bulletin of Public Health, 2023)
A healthy lifestyle is a rational lifestyle, an integral feature of which is vigorous activity aimed at maintaining and improving health. A lifestyle that promotes public and individual health is the basis of prevention, and its formation is the most important task of the state’s social policy in protecting and strengthening the health of the people.